Loganin ameliorates cartilage degeneration and osteoarthritis development in an osteoarthritis mouse model through inhibition of NF-κB activity and pyroptosis in chondrocytes. (30th January 2020) - Hu, Jiaming; Zhou, Jinyi; Wu, Jinting; Chen, Quan; Du, Weibin; Fu, Fangda; Yu, Huan; Yao, Sai; Jin, Hongting; Tong, Peijian; Chen, Di; Wu, Chengliang; et al.
Abstract: Ethnopharmacological relevance: Corni Fructus (CF), the red fruit of Cornus officinalis Siebold & Zucc, has been used both as food and medicinal herb in traditional Chinese medicine (TCM). Loganin is a major iridoid glycoside and one of the quality control indexes of CF. In TCM clinical practice, prescription containing CF is commonly used to treat osteoarthritis (OA), but the underlying mechanisms of loganin are not yet utterly understood. Aim of the study: The aims of the present study are to confirm the therapeutic effects of loganin in an OA mouse model and to determine the mechanisms involved in the OA protective effects. Materials and methods: The destabilization of the medial meniscus (DMM) procedure was performed on the right knee of 8-week-old C57BL/6 male mice. 30 or 100 μg/ml of loganin was then injected into articular space twice a week for 8 and 12-week. Safranin O/Fast green staining, H&E staining, micro-CT analysis were performed to analyze structural and morphological changes. The protein expression of collagen type II (Col2), metalloproteinase-3 (Mmp3), matrix metalloproteinase 13 (Mmp13) collagen type X (Col10), cryopyrin and caspase-1 were detected by immunochemistry staining. Immuno-fluorescence assay was performed to assess changes in expression of CD31, endomucin, p65 and p-I-κB. Results: Results of histomorphometry showed that loganin delays the progression of OA in the DMM model. In cartilage, loganin decreased the OARSI score, increasing hyaline cartilage (HC) thickness and decreasing calcified cartilage (CC) thickness. Moreover, loganin inhibited osteophyte formation, reduced the bone volume fraction (BV/TV), lowered trabecular thickness (Tb.Th) and increased trabecular separation (Tb.Sp) in subchondral bone. Mechanistically, loganin increased the expressions of Col2, decreases the expression of Mmp3, Mmp13, Col10, cryopyrin and caspase-1 in cartilage. In parallel, loganin inhibited the expression of CD31 and endomucin in subchondral bone. Furthermore, loganin suppressed nuclear translocation of p65 protein, and decreased the amount of p-I-κB in chondrocytes. Conclusions: In summary, these results uncovered that loganin inhibits NF-κB signaling and attenuates cartilage matrix catabolism and pyroptosis of chondrocytes in articular cartilage. Loganin may serve as a potential therapeutic agent for OA treatment. Graphical abstract: Image 1